THE CONTENT KNOWLEDGE ABILITY OF SCIENCE TEACHER CANDIDATES: THE ANALYSIS OF LEARNING MEDIA DEVELOPMENT - Lina Arifah Fitriyah; Nur Hayati; Andri Wahyu Wijayadi (Program Studi Pendidikan IPA, Fakultas Ilmu Pendidikan, Universitas Trunojoyo Madura, 2020)
In the teaching and learning process, an educator must be creative and can use engaging learning media. Learning media is expected to be able to help educators to deliver the subject matter well. Therefore, an educator (teacher) must have the minimum skills, proficiency, and expertise that meet specific standards and competencies. One of the gifts is content knowledge. Content Knowledge (CK) is the initial ability of an educator that should be mastered in mastering learning material (understanding of material concepts). To master the ability of good content knowledge in science teacher candidates, one can see from the students' ability to create and compile learning media. This study aims to: determine (1) the ability of content knowledge of science teacher candidates in making learning media based on indicators, and (2) the significance of content knowledge of science teacher candidates in making learning media. The research method used is a quantitative description. The research subjects were 15 students of the Science Education Study Program in the academic year 2018. The research instrument used was the content knowledge assessment sheet. The results showed that: (a) the ease of media used 75.73% (good category), the suitability of the media with the characteristics of students 77.53% (good), the accuracy of the media with the material and learning objectives 73% (good), and the attractiveness of the media 80.67 % (well). It also showed that (b) there is a significant difference in students' content knowledge in making learning media with significant value (2-tailed) 0,05, which is 0,000.